2012
DOI: 10.5604/17322693.1003484
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry in the etiology of autoimmune diseases

Abstract: There are currently more than 80 different autoimmune diseases, affecting approximately 100 million people worldwide. The etiology of most autoimmune diseases is unknown. The highest incidence of these diseases is in the developed countries and they are more common in women than in men. Among the most often listed factors responsible for the onset of autoimmunity are genetic predisposition and the phenomenon known as molecular mimicry. The latter stems from a similarity between microbial antigens and antigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The similarities that exist between antigens of microorganisms and antigens (autoantigens) in the human body is a homology which may lead to the generation of autoantibodies and then to the crossdevelopment reaction which consequently triggers an autoimmune disease by targeting the immune system against its tissues. However, these similarities between antigens do not always result in autoimmune disorders [4]. Other factors include psychological stress and dietary aspect [7].…”
Section: Factors Causing Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarities that exist between antigens of microorganisms and antigens (autoantigens) in the human body is a homology which may lead to the generation of autoantibodies and then to the crossdevelopment reaction which consequently triggers an autoimmune disease by targeting the immune system against its tissues. However, these similarities between antigens do not always result in autoimmune disorders [4]. Other factors include psychological stress and dietary aspect [7].…”
Section: Factors Causing Autoimmune Diseasesmentioning
confidence: 99%
“…Epidemiological studies conducted over the last few years prove that 3-8% of people from the entire population develop autoimmune disorders [2] and in this group the most common diseases (about 94%) are: Hashimoto's thyroiditis, Graves' disease, Diabetes mellitus type 1, Pernicious anaemia, Rheumatoid arthritis, Acquired vitiligo, Systemic lupus erythematosus and Multiple sclerosis [3]. The list of diseases is very long and according to various sources can contain from 80 [4] to even more than 150 disease entities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 80 autoimmune diseases have effect on approximately 100 million people worldwide [ 9 ], and among these diseases T1D, MS, RA and SLE are more common and more investigative. In summary, the significance of this research is to study the shared and specific characteristics of the four diseases by analyzing the shared and specific pathways and discovering the shared and specific pathological mechanism based on systems biology, that through integrating data of genetic level (such as expression profiling, SNP) and epigenetic level (such as methylation, miRNA), to mine disease-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Other pathogenic organisms, such as rubella infection, enteroviruses, human cytomegalovirus, and rotavirus, have all been suggested to play a role in cross-reactivity leading to pancreatic islet cell destruction [ 13 ]. Cross-reactivity is thought to occur when antigens share amino acid sequence homology with self-tissue proteins in susceptible hosts and has been theorized as a trigger for tissue-specific autoimmune diseases [ 14 16 ]. Immunological cross-reactivity was first identified in 1942 when it was found that individuals sensitized to pollen allergens developed immune reactivity to specific fruits [ 17 ].…”
Section: Introductionmentioning
confidence: 99%